Asbestos and other natural mineral fibres (Geneva, 1986)
Assesses the health risks associated with exposure to asbestos and other natural mineral fibres. Because of the well-documented association between occupational exposure to asbestos and the development of serious disease, the book concentrates on the detection of points of inconsistency or consensus in the literature that can be used to develop a more precise understanding of health hazards. A section devoted to experimental work reviews the considerable body of toxicological data available from studies in animals and cell systems, emphasizing new findings that help elucidate the mechanisms of toxicity. The book also cites convincing evidence that erionite is an especially hazardous carcinogen.